A comprehensive assessment of the global warming potential of geopolymer concrete. (15th May 2021) - Shobeiri, Vahid; Bennett, Bree; Xie, Tianyu; Visintin, Phillip
Abstract: Approximately 5%–7% of global Carbon Dioxide (CO2 ) emissions can be attributed to Ordinary Portland Cement (OPC), which has traditionally been used as the primary binder in concrete. Geopolymer concrete has been widely claimed to have lower global warming potential than OPC concrete, and this claim has formed the basis of many studies examining mix designs and mechanical properties of geopolymer concretes. A major limitation with the vast majority of existing studies is a lack of the direct quantification of the global warming potential of the materials developed. That is, the underlying assumption in the majority of these studies is that geopolymer concrete is more sustainable than OPC based concretes. The aim of this paper is to quantify the CO2 equivalent (CO2-eq ) emissions associated with production of a large number of previously developed mix designs (1404 mix designs from 110 studies) including the impacts of curing, allocation and transportation and allowing for variation in energy grid source and the production of the activator solution. When considering the impact of transportation, a case study based on five major capital cities in Australia is presented and the critical transport distances at which the manufacture of geopolymers becomes more emissions intensive than conventional concrete is identified. The results show that the relative CO2-eq emissions of geopolymer and OPC based concretes of the same strength, are highly dependent on the system boundary for analysis, the type of allocation scenario and material transportation distances and mode, and further, that depending on these factors geopolymer concretes can either have significantly lower, or significantly higher CO2-eq emissions than OPC concretes of the same strength. It is expected that the findings of this work can aid in specifying the optimal concrete types for reducing CO2-eq emissions considering the intended use of the concrete.